ACTUAL PROBLEMS AND ACHIEVEMENTS OF FUNDAMENTAL AND PRACTICAL KNOWLEDGE - Akramova Parvina Aminovna; G’afforova Dilshoda Ikromjon qizi (TADQIQOTLAR.UZ, 2024)
Annotation. This text explores the challenges and successes associated with two types of knowledge: fundamental and applied. Fundamental knowledge refers to the underlying principles and theories that govern a particular field, while applied knowledge focuses on using those principles to solve practical problems. The text likely discusses the importance of both types of knowledge for scientific and technological advancement, along with specific examples of how each has addressed real-world issues.